2021
DOI: 10.33160/yam.2021.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cervical Ultrasonography in Globus Sensation Investigation: A Retrospective Cohort Study

Abstract: Background A globus sensation is one of the most common complaints in otolaryngological practice. Patients with no associated abnormalities detected during the usual examinations performed in ENT clinics, are being diagnosed with globus sensation. Cervical ultrasonography is usually not performed in ENT clinics; however, it is useful in screening diseases of the subcutaneous tissue/organs, whose detection is not possible with the routine ENT examinations. The purpose of our study was to elucidate whether cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
2
0
0
Order By: Relevance
“…37 In addition, another study using ultrasound in ENT patients only also found a low incidence of cancer in patients with GP. 38 These results align with the ones from our study, because those who underwent workup without worsening symptoms did not develop HN cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…37 In addition, another study using ultrasound in ENT patients only also found a low incidence of cancer in patients with GP. 38 These results align with the ones from our study, because those who underwent workup without worsening symptoms did not develop HN cancer.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study which evaluated the population of an ENT center assessing the benefits of ultrasound versus videofluroscopy found that those with chronic symptoms did not develop HN cancer 37 . In addition, another study using ultrasound in ENT patients only also found a low incidence of cancer in patients with GP 38 . These results align with the ones from our study, because those who underwent workup without worsening symptoms did not develop HN cancer.…”
Section: Discussionsupporting
confidence: 90%